2006
DOI: 10.1037/1541-1559.3.4.249
|View full text |Cite
|
Sign up to set email alerts
|

The ability of the MMPI-2 to detect feigned PTSD within the context of compensation seeking.

Abstract: The ability of the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) validity scales to detect feigned reports of posttraumatic stress disorder (PTSD) was examined in a group of veterans undergoing a compensation and pension evaluation. Veterans who were seeking compensation for service connected PTSD were randomly assigned to one of two groups: exaggerate PTSD and respond honestly. The MMPI-2 Infrequency (F) family of scales was able to accurately identify the veterans instructed to exaggerate PTSD. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 58 publications
4
27
0
Order By: Relevance
“…Note that the Conservative Cut scores are, indeed, very conservative scores. For example Arbisi, Ben-Porath, and McNulty (2006) found that lower cut scores successfully differentiated compensation-seeking veterans instructed to answer MMPI-2 items honestly versus those instructed to exaggerate PTSD symptoms and avoid detection. Rubenzer (2009) is another resource to consult as the author recommends a specific response-style battery to assess for feigned PTSD.…”
Section: Screening and Assessment Of Exaggeration And Feigningmentioning
confidence: 99%
“…Note that the Conservative Cut scores are, indeed, very conservative scores. For example Arbisi, Ben-Porath, and McNulty (2006) found that lower cut scores successfully differentiated compensation-seeking veterans instructed to answer MMPI-2 items honestly versus those instructed to exaggerate PTSD symptoms and avoid detection. Rubenzer (2009) is another resource to consult as the author recommends a specific response-style battery to assess for feigned PTSD.…”
Section: Screening and Assessment Of Exaggeration And Feigningmentioning
confidence: 99%
“…Additionally, the F scale is highly correlated with depression, PTSD and dissociation-all of which are common among adult victims of trauma exposure, such as sexual abuse (Klotz Flitter et al 2003). Nonetheless, these F-related scales appear to have better malingered PTSD detection accuracy than other scales such as FBS and Ds, a finding consistent across studies discriminating simulated PTSD among college students and clinical samples from outpatients with military-and civilian-related PTSD (Arbisi et al 2006;. Rogers et al (2003) published a meta-analysis of malingering on the MMPI-2.…”
Section: Detecting Malingered Ptsdmentioning
confidence: 60%
“…After the Rogers et al (2004) metaanalysis was published, several studies found respectable accuracy rates for detecting malingered PTSD. Specifically, the MMPI-2's Fp scale has demonstrated accuracy in the 80-90% range based on a T-score cutoff of 85 or higher, from studies comparing VA disability compensation seeking military veterans instructed to simulate PTSD or respond honestly (Arbisi et al 2006), trauma victims simulating PTSD vs. genuine workplace injury claimants (Efendov et al 2008), and college students simulating PTSD vs. genuine workplace injury claimants (Marshall and Bagby 2006).…”
Section: Detecting Malingered Ptsdmentioning
confidence: 99%
“…Grieffenstein et al ( 2004 ) found that the FBS was superior to other MMPI-2 validity indicators in detecting evaluees with improbable trauma claims. However, Arbisi et al ( 2006 ) found that the FBS did not add incrementally to validity with respect to other MMPI-2 validity scales in predicting simulation or exaggeration of symptoms of PTSD. The Fptsd was created for detecting simulated PTSD in combat veterans (Elhai et al 2002 ), but it has not been found effective with civilian populations (Arbisi et al 2006 ;Elhai et al 2002Elhai et al , 2004Marshall and Bagby 2006 ).…”
Section: Morel (2010)mentioning
confidence: 79%
“…However, Arbisi et al ( 2006 ) found that the FBS did not add incrementally to validity with respect to other MMPI-2 validity scales in predicting simulation or exaggeration of symptoms of PTSD. The Fptsd was created for detecting simulated PTSD in combat veterans (Elhai et al 2002 ), but it has not been found effective with civilian populations (Arbisi et al 2006 ;Elhai et al 2002Elhai et al , 2004Marshall and Bagby 2006 ). The PAI also has several validity indicators, but Morel ( 2010 ) argued that the research indicates that a degree of caution is necessary in using it in malingered PTSD detection.…”
Section: Morel (2010)mentioning
confidence: 79%